2014
DOI: 10.1371/journal.pone.0085566
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Turnover in Stable Coronary Artery Disease – Influence of Thrombopoietin and Low-Grade Inflammation

Abstract: BackgroundNewly formed platelets are associated with increased aggregation and adverse outcomes in patients with coronary artery disease (CAD). The mechanisms involved in the regulation of platelet turnover in patients with CAD are largely unknown.AimTo investigate associations between platelet turnover parameters, thrombopoietin and markers of low-grade inflammation in patients with stable CAD. Furthermore, to explore the relationship between platelet turnover parameters and type 2 diabetes, prior myocardial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 41 publications
5
37
0
1
Order By: Relevance
“…In our study, %RP strongly correlated with CRP. These data can be supported by the results of Larsen et al who recently demonstrated positive correlation between hsCRP and immature platelet count as well as with thrombopoietin level [15]. Even though vWF Ag values were higher by 5 % in diabetics, they did not correlate with %RP which is in accordance to previous data [14].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our study, %RP strongly correlated with CRP. These data can be supported by the results of Larsen et al who recently demonstrated positive correlation between hsCRP and immature platelet count as well as with thrombopoietin level [15]. Even though vWF Ag values were higher by 5 % in diabetics, they did not correlate with %RP which is in accordance to previous data [14].…”
Section: Discussionsupporting
confidence: 88%
“…Mean values of %RP in these studies can't be compared to the mean values of %RP obtained by CELL-DYNN Sapphire. Mean values of %RP in our both groups of patients can't be compared with the results of the studies [9,14,15] where IPF was determined by Sysmex technology and one must observe that these studies did not separate diabetics from non-diabetic patients.…”
Section: Discussionmentioning
confidence: 90%
“…Levels were elevated in patients within 24 h after ischemic stroke compared to normal controls [28]. Increased TPO levels have also been noted in diabetics, and stable and unstable cardiovascular disease [29,30]. In our study, the TPO levels were not significantly different in RTR with or without diabetes or a history of cardiovascular disease; however, they were associated with the CRCRTR-MACE score, which calculates the cumulative CV-risk based on these and other risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…[5] The Platelet Indices (PIs) are believed to have a role in predicting the clinical course in various disease states: from infectious, inflammatory, metabolic to even acute abdomen; and in many of these conditions, platelets are presumed to play a pathogenic role. [6][7][8][9][10] Furthermore, PIs are considered valuable in suggesting the pathophysiologic mechanism of thrombocytopenia. [11] Also, in dengue it is believed to have value in diagnosing and classifying the disease into Dengue Fever (DF) and Severe Dengue.…”
Section: Introductionmentioning
confidence: 99%